Hyaluronidase in Clinical Isolates of Propionibacterium acnes. (18th February 2015) - Tyner, Harmony; Patel, Robin
Abstract : Objectives . We sought to describe the prevalence of a hyaluronidase gene and hyaluronidase production in 197 clinical isolates of P. acnes ; we assessed kinetics of hyaluronidase production in a subset of three isolates. Methods . The hyaluronidase gene was detected using polymerase chain reaction. Hyaluronidase production was detected by growing isolates on BHI agar containing 400 μ g/mL hyaluronic acid and 1% albumin and flooding plates with 2 N glacial acetic acid to precipitate unbound hyaluronic acid, with a zone of clearing representing a positive phenotype. Hyaluronidase production kinetics were measured as a function of hyaluronic acid digestion over time in a liquid medium. Results . A hyaluronidase gene and hyaluronidase production were detected in 100 and 97% of P. acnes isolates, respectively. Hyaluronidase production in liquid medium was detectable after 96 hours of growth. Conclusions . Hyaluronidase production is nearly universal among P. acnes isolates. Three days appear to be required for significant hyaluronidase production in a liquid medium. Detection of hyaluronidase in tissue specimens may be a strategy to differentiate P. acnes infection from colonization when P. acnes is isolated from a clinical specimen.